Steiner’s December Triangle

Geometry Level pending

As shown in the figure, an equilateral triangle inscribes seven circles, three with a radius of r 1 r_1 , three with a radius of r 3 r_3 , and the central circle has a radius of r 2 r_2 .

If r 2 + r 3 r 1 = a ( c + d e ) b \dfrac{r_2+r_3}{r_1} = \dfrac{a(c+d\sqrt e)}b , where a a , b b , c c , d d , and e e are positive integers with a a and b b being coprime and e e square-free, find a + b + c + d + e a+b+c+d+e .

Inspiration


The answer is 20.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Chew-Seong Cheong
Dec 14, 2020

Label the equilateral triangle A B C ABC and the center of the central circle with radius r 2 r_2 be O O . Due to symmetry, center O O is also the centroid of A B C \triangle ABC . Let the side length of A B C \triangle ABC be 1 1 . Then A O = B O = C O = 1 3 AO=BO=CO=\frac 1{\sqrt 3} and O N = 1 2 3 ON = \frac 1{2\sqrt 3} , where B N BN is a median of A B C \triangle ABC . Then we have:

{ 3 r 3 + r 2 = 1 3 . . . ( 1 ) 2 r 1 + r 2 = 1 2 3 . . . ( 2 ) ( 1 ) ( 2 ) : 3 r 3 2 r 1 = 1 2 3 \begin{cases} 3r_3 + r_2 = \dfrac 1{\sqrt 3} & ...(1) \\ 2r_1 + r_2 = \dfrac 1{2\sqrt 3} & ...(2) \end{cases} \implies (1) - (2) : \quad 3r_3 - 2r_1 = \frac 1{2\sqrt 3}

Let the center of the left-bottom circle with radius r 3 r_3 be P P and P M PM be perpendicular to A C AC . Then we have

A M + M N = A N 3 r 3 + ( r 3 + r 1 ) 2 ( r 3 r 1 ) 2 = 1 2 3 r 3 + 2 r 1 r 3 = 1 2 2 r 1 r 3 = 1 2 3 r 3 Squaring both sides 4 r 1 r 3 = 3 r 3 2 3 r 3 + 1 4 Multiply both sides by 4 16 r 1 r 3 = 12 r 3 2 4 3 r 3 + 1 Since 3 r 3 2 r 1 = 1 2 3 8 ( 3 r 3 1 2 3 ) r 3 = 12 r 3 2 4 3 r 3 + 1 24 r 3 2 4 3 r 3 = 12 r 3 2 4 3 r 3 + 1 12 3 r 3 2 + 8 r 3 3 = 0 r 3 = 64 + 144 8 24 3 = 13 2 6 3 r 2 = 1 3 3 r 3 = 4 13 2 3 r 1 = 1 4 3 r 2 2 = 13 3 4 3 r 2 + r 3 r 1 = 2 ( 1 + 13 ) 3 \begin{aligned} AM + MN & = AN \\ \sqrt 3 r_3 + \sqrt{(r_3+r_1)^2 - (r_3-r_1)^2} & = \frac 12 \\ \sqrt 3 r_3 + 2 \sqrt{r_1r_3} & = \frac 12 \\ 2 \sqrt{r_1r_3} & = \frac 12 - \sqrt 3 r_3 & \small \blue{\text{Squaring both sides}} \\ 4r_1r_3 & = 3r_3^2 - \sqrt 3 r_3 + \frac 14 & \small \blue{\text{Multiply both sides by }4} \\ \blue{16r_1}r_3 & = 12r_3^2 - 4\sqrt 3 r_3 + 1 & \small \blue{\text{Since }3r_3 - 2r_1 = \frac 1{2\sqrt 3}} \\ \blue{8\left(3r_3-\frac 1{2\sqrt 3}\right)}r_3 & = 12r_3^2 - 4\sqrt 3 r_3 + 1 \\ 24r_3^2 - \frac 4{\sqrt 3} r_3 & = 12r_3^2 - 4\sqrt 3 r_3 + 1 \\ 12\sqrt 3 r_3^2 + 8r_3 - \sqrt 3 & = 0 \\ \implies r_3 & = \frac {\sqrt{64+144}-8}{24\sqrt 3} = \frac {\sqrt{13}-2}{6\sqrt 3} \\ r_2 & = \frac 1{\sqrt 3} - 3r_3 = \frac {4-\sqrt{13}}{2\sqrt 3} \\ r_1 & = \frac 1{4\sqrt 3} - \frac {r_2}2 = \frac {\sqrt{13}-3}{4\sqrt 3} \\ \implies \frac {r_2+r_3}{r_1} & = \frac {2(1+\sqrt{13})}3 \end{aligned}

Therefore a + b + c + d + e = 2 + 3 + 1 + 1 + 13 = 20 a+b+c+d+e = 2+3+1+1+13 = \boxed{20} .

@Michael Huang , you have to mention that the triangle is equilateral. If a a and b b are non-zero integers, then a = 2 a=-2 and b = 3 b=-3 are also valid solutions that a + b + c + d + e = 10 a+b+c+d+e = 10 . I have amended the problem statement for you.

Chew-Seong Cheong - 6 months ago

Log in to reply

Yes. Thank you very much for the info.

Michael Huang - 6 months ago
Hosam Hajjir
Dec 13, 2020

Since we're interested in ratios, we can take the side length of the triangle to be 1 1 . Then we can write the following three relations involving r 1 , r 2 r_1 , r_2 and r 3 r_3

2 r 1 + r 2 = 1 2 3 ( 1 ) 2 r_1 + r_2 = \dfrac{1}{2 \sqrt{3} } \hspace{24 pt} (1)

r 2 + 3 r 3 = 1 3 ( 2 ) r_2 + 3 r_3 = \dfrac{1}{\sqrt{3}} \hspace{24 pt} (2)

( r 1 + r 3 ) 2 = ( r 1 r 3 ) 2 + ( 3 r 3 1 2 ) 2 ( 3 ) (r_1 + r_3)^2 = (r_1 - r_3)^2 + ( \sqrt{3} r_3 - \frac{1}{2} )^2 \hspace{24 pt} (3)

Solving the first two equations, results in:

( r 1 , r 2 , r 3 ) = ( 1 4 3 , 1 3 , 0 ) + t ( 3 2 , 3 , 1 ) (r_1 , r_2, r_3 ) = ( -\dfrac{1}{4 \sqrt{3} } , \dfrac{1}{\sqrt{3} } , 0 ) + t ( \dfrac{3}{2}, -3 , 1 )

Pluggin this into equation (3), results in a quadratic equation in t t , which solves to

t = 1 6 3 ( 13 2 ) t = \dfrac{1}{6 \sqrt{3} } ( \sqrt{13} - 2 )

The required ratio is r 2 + r 3 r 1 = 1 3 2 t 1 4 3 + 3 2 t \dfrac{r_2 + r_3}{r_1} = \displaystyle \dfrac{ \frac{1}{\sqrt{3}}-2 t} {-\frac{1}{4 \sqrt{3} } +\frac{3}{2} t}

Pluggin in the value of t t we obtained into the above quotient, and simplifying, results in:

r 2 + r 3 r 1 = 2 3 ( 1 + 13 ) \dfrac{r_2 + r_3}{r_1} = \frac{2}{3} (1 + \sqrt{13} )

Hence, a = 2 , b = 3 , c = 1 , d = 1 , e = 13 a = 2, b = 3, c = 1 , d = 1, e = 13 , and this makes the answer 20 \boxed{20 }

David Vreken
Dec 22, 2020

Let r 1 = 1 r_1 = 1 , r 2 = x r_2 = x , r 3 = y r_3 = y , and label the diagram as follows:

From right A B F \triangle ABF we know that A B = B F cos 60 ° = 2 y AB = \frac{BF}{\cos 60°} = 2y .

From right A C E \triangle ACE we know that A C = C E cos 60 ° = 2 x + 4 AC = \frac{CE}{\cos 60°} = 2x + 4 , and since A C = 3 y + x AC = 3y + x , 2 x + 4 = 3 y + x 2x + 4 = 3y + x or x = 3 y 4 x = 3y - 4 .

By the law of cosines on B C D \triangle BCD , B D 2 = B C 2 + C D 2 2 B C C D cos 60 ° BD^2 = BC^2 + CD^2 - 2 \cdot BC \cdot CD \cos 60° , or ( y + 1 ) 2 = ( x + y ) 2 + ( x + 1 ) 2 ( x + y ) ( x + 1 ) (y + 1)^2 = (x + y)^2 + (x + 1)^2 - (x + y)(x + 1) .

These two equations solve to x = 1 2 ( 13 1 ) x = \frac{1}{2}(\sqrt{13} - 1) and y = 1 6 ( 7 + 13 ) y = \frac{1}{6}(7 + \sqrt{13}) .

Therefore, r 2 + r 3 r 1 = x + y 1 = 2 ( 1 + 13 ) 3 \cfrac{r_2 + r_3}{r_1} = \cfrac{x + y}{1} = \cfrac{2(1 + \sqrt{13})}{3} , so that a = 2 a = 2 , b = 3 b = 3 , c = 1 c = 1 , d = 1 d = 1 , e = 13 e = 13 , and a + b + c + d + e = 20 a + b + c + d + e = \boxed{20} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...